Influence of learning activities and background characteristics on pharmacology exam success in second-year medical students at a French university: the Pharmaquest study - Dumont, Jean-Marie; Chretien, Basile; Morice, Pierre‐Marie; Saillot, Eric; Humbert, Xavier; Legallois, Damien; Aleksić, Branko; Kasuya, Hideki; Fédrizzi, Sophie; Alexandre, Joachim; Lelong‐Boulouard, Véronique; Dolladille, Charles (BMC Medical Education, 2026)
BACKGROUND: Pharmacology education faces challenges due to evolving student learning behaviors. This study examined the feasibility of identifying which student-level characteristics, academic background and learning activities were associated with performance at the pharmacology exam using routinely-collected data. METHODS: In a prospective cohort study of second-year medical students at Caen Normandie University (2024-2025), we analyzed in-person lecture, online resource, and peer tutoring mock exam attendance, as well as use of student-written lecture support, and pharmacology exam outcomes. The primary outcome was final pharmacology exam score (over 20points), according to pedagogical methods, estimated through multivariate linear regression. RESULTS: year medical students, with two thirds of women, high prior academic achievement, and a median age of 19. In the univariate analysis, higher in-person lecture attendance was significantly associated with a higher score at the pharmacology exam (+ 0.41points for each additional 10h of attendance, 95%Confidence Interval (CI): + 0.05 to + 0.77). Similarly, the number of online resources downloaded showed a positive association in univariate analysis (+ 0.53points for each additional 10downloads, 95%CI: + 0.09 to + 0.97). In-person lecture attendance remained significant in the multivariate model (+ 0.46points, 95%CI:0.03-0.88). Peer tutoring exam attendance and student-written lecture support use were not associated with a significant change in exam score. In-person lecture attendance exhibited a U-shaped relationship with exam performance: initial declines (up to 10h) preceded gradual improvement, plateauing at 25-30 h (spline regression, p < 0.05). Prior academic achievement (baccalaureate distinction, rapid first-year completion) and curriculum (first-year major being health-science) were significantly associated with higher exam score. CONCLUSIONS: This pilot study demonstrates the feasibility and value of quantitatively evaluating pharmacology education among French medical students. Academic background and pedagogical methods seem to influence pharmacology exam success. Broader replication, and long-term follow-up are needed to confirm these insights and identify determinants of student success more robustly.